2001
DOI: 10.1007/s002460010257
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I and N-Terminal Pro-Brain Natriuretic Peptide in Umbilical Artery Blood in Relation to Fetal Heart Rate Abnormalities During Labor

Abstract: The use of continuous fetal heart rate (FHR) recordings to monitor fetal well-being during labor is standard clinical practice in developed countries. Little is known about the relationship, if any, that exists between these FHR abnormalities and the fetal cardiac musculature and function. The aim of this study was to investigate umbilical artery serum levels of cardiac troponin I, a sensitive and specific marker of myocardial necrosis, and N-terminal pro-brain natriuretic peptide (pro-BNP), a sensitive marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…121 Existing data suggest a strong correlation between natriuretic peptide measurement and myocardial dysfunction following standard dose anthracycline chemotherapy. 122,123 Importantly, unlike cTn's, BNP elevation may reflect chemotherapy-associated diastolic abnormalities 123,124 and the level may be increased by myocardial stress without necrosis, 125 thus potentially increasing their sensitivity over that afforded by cTn's. In the HD chemotherapy setting, patients who developed clinical heart failure exhibited elevated plasma BNP level in several measurements before the onset of signs/symptoms, although lesser elevations, and only on a single measurement were detected also in patients who did not experience cardiac toxicity.…”
Section: Circulating Markersmentioning
confidence: 99%
“…121 Existing data suggest a strong correlation between natriuretic peptide measurement and myocardial dysfunction following standard dose anthracycline chemotherapy. 122,123 Importantly, unlike cTn's, BNP elevation may reflect chemotherapy-associated diastolic abnormalities 123,124 and the level may be increased by myocardial stress without necrosis, 125 thus potentially increasing their sensitivity over that afforded by cTn's. In the HD chemotherapy setting, patients who developed clinical heart failure exhibited elevated plasma BNP level in several measurements before the onset of signs/symptoms, although lesser elevations, and only on a single measurement were detected also in patients who did not experience cardiac toxicity.…”
Section: Circulating Markersmentioning
confidence: 99%
“…Additionally, it may also help to regulate the blood supply to the fetus and modulate myocite growth during development [8,9]. As an alternative to BNP, NT-proBNP may have some advantages, namely a longer half-life and greater stability [10,11]. Natriuretic peptides are thought not to cross the placenta and therefore any variation in neonates must be explained intrinsically [7].…”
Section: Introductionmentioning
confidence: 98%
“…However, in children the knowledge about the significance of plasma levels of NT-proBNP is still limited. In healthy children, studies have shown that NT-proBNP levels are elevated soon after birth reaching its peak at 24 h of life decreasing thereafter up to 4 months and remaining unchanged until the age of 15 [15][16][17][18][19] . NT-proBNP levels are elevated in children with congenital heart disease or cardiomyopathy [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%